Cost-effectiveness of facilitated access to a self-management website (HeLP-Diabetes) compared to usual care for patients with Type 2 Diabetes: a randomised-control trial - Li, J; Parrott, S; Sweeting, M; Farmer, A; Ross, J; Dack, C; Pal, K; Yardley, L; Barnard, M; Hudda, M; Alkhaldi, G; Murray, E (JMIR Publications, 2018)
Background: Type 2 Diabetes Mellitus is one of the commonest long term conditions, and costs health services approximately 10% of their total budget. Active self-management by patients improves outcomes and reduces health service costs. The uptake of face-to-face self-management education is low, and there is hope that delivering self-management support online may improve this. Objective: To establish the cost-effectiveness of a web-based self-management programme for people with type 2 Diabetes (HeLP-Diabetes) compared to usual care. Methods: An incremental cost-effectiveness analysis was conducted, from a collective National Health Service and personal social services perspective, based on data collected from a multi-centre, two-arm individually randomised controlled trial over 12 months. Adults aged 18 or over with a diagnosis of type 2 diabetes and registered with the 21 participating general practices (primary care) in England, UK, were approached. People who were unable to provide informed consent or to use the intervention, terminally ill, or currently participating in a trial of an alternative self-management intervention, were excluded. The participants were then randomised to usual care plus either nurse-facilitated access to HeLP-Diabetes, an interactive, theoretically-informed web-based self-management programme, or access to a comparator web-site containing basic information only with an initial nurse-facilitated session. Participants were blinded to their allocation. The participants’ intervention costs and wider health care resource use were collected as well as two self-reported health-related quality of life measures: the Problem Areas in Diabetes (PAID) Scale and EQ-5D-3L. EQ-5D-3L was then used to calculate quality-adjusted life years (QALYs). The primary analysis was based on intention-to-treat, using multiple imputation to deal with the missing data. Results: In total, 374 participants were randomised, with 185 in the intervention group and 189 in the control group. The primary analysis showed incremental cost-effectiveness ratios (ICERs) of £58 (-£268 to £742) per unit improvement on PAID scale and £5,550 (-£15,515 to £59,275) per QALY gained by HeLP-Diabetes, compared to the control. The complete case analysis showed less cost-effectiveness and more uncertainty with ICERs of £116 (95% CI -£1,299 to £1,690) per unit improvement on PAID scale and £18,500 (95%CI -£203,949 to £190,267) per QALY. The cost-effectiveness acceptability curve showed an 87% probability of cost-effectiveness at £20,000 per QALY willingness-to-pay threshold. Cost-effectiveness was highly sensitive to the number of users, with the one-way sensitivity analysis suggesting that the intervention would become less costly than usual care with 363 or more users. Conclusion: Facilitated access to HeLP-Diabetes is cost-effective, compared to usual care, under the recommended threshold of £20,000 to £30,000 per QALY by National Institute of Health and Care Excellence. The effect of economies of scale suggests very low costs per user with sufficient number of users.